Impacts of climate change and variability on rural livelihoods and adaptation strategies in Ethiopia: a review paper - Daba, Belay; Regasa, Tena; Mammo, Siraj (Frontiers in Climate, 2025)
Climate change and variability are changes in the state of climate and weather conditions due to anthropogenic and physical factors. The main aim of this review paper is to examine the impacts of climate change and variability on rural livelihood and adaptation strategies employed in southern Ethiopia. In this review paper, the selection of literature was mainly based on search engines and raised areas from Google Scholar, Web of Science, Research Gate, Science Direct, and many other scientific journal publishing websites. This review focuses on climate change and variability in southern Ethiopia, highlighting its impact on rural livelihoods and adaptation strategies. Climate change and its variability affect sub-Saharan countries such as Ethiopia, crop production, livestock rearing, land productivity, water availability, biotic growth, rangeland quality, and soil productivity. This was due to rain-fed agricultural activity, low adaptation capacity, less attention given to policy development/implementation, lack of awareness, lack of modern agricultural input, and lack of effective, and efficient technology, etc. Ethiopian rural livelihoods need a comprehensive approach to mitigate climate change impacts. Mitigation should focus on sustainable agriculture, renewable energy, and non-farm activities, while adaptation involves livelihood diversification, early warning systems, community-based initiatives, policy frameworks, and capacity-building programs. Despite adaptation measures such as cropping practices, modern input, crop diversification, and land management, climate change variability remains severe in Ethiopia, particularly in pastoral and semi-pastoral regions. The reviewer suggested that the government, NGOs, community, and private organizations should work together to address climate change and variability, focusing on enhancing adaptive capacity and sustainable environments.